Development and evaluation of a culturally sensitive food frequency questionnaire for the assessment of prebiotic and probiotic intake of urban-living, low-to-medium-income women - Bayaga, Cecile Leah T.; Gabriel, Alonzo A.; Bongga, Demetria C.; Pico, Marietoni B.; Barrios, Erniel B. (2019)
Modern food product development has introduced maternal consumers to functional foods. Prebiotics and probiotics are well-known functional food components. This study developed a culturally sensitive, qualitative food frequency questionnaire (FFQ) to assess the prebiotic and probiotic intakes of healthy, urban-living Filipino women. Food items in the developed FFQ were based on five datasets of information. Reproducibility was tested by comparing respondents? (n=73) responses on Day 30 (FFQ1) and Day 31 (FFQ2). Verification of the developed tool was conducted by comparing responses from the FFQs with multiple food recalls obtained from the same respondents and sampling time. Thirteen (13) food groups with 39 unique food items were included in the developed FFQ. Binomial results showed matched responses of food items (38/39) between FFQ1 and FFQ2. Comparison of the results of FFQ and multiple food recalls showed highly similar responses. The developed FFQ to assess prebiotic and probiotic intakes of women was reproducible and has been verified. (Author's abstract)